Innovations in Drug Spectroscopy Methods for Pharmaceutical Compounds: Inovasi dalam Metode Spektroskopi Obat untuk Senyawa Farmasi - Aldabag, Huda Faeq Hasan; Kamaluldeen, Abdullah; Ahmed, Saif Ali; Alzurfi, Talib abbas (Indonesian Journal on Health Science and Medicine, 2024)
General Background: Spectroscopy is a pivotal analytical technique in pharmaceutical research, enabling precise analysis of molecular structures and compositions through the interaction of light with matter. Specific Background: Spectroscopic methods have significantly advanced pharmaceutical analysis since the mid-20th century, addressing challenges like drug resistance and the need for improved drug purity and stability. Techniques such as UV-Visible, Fourier Transform Infrared (FTIR), and Nuclear Magnetic Resonance (NMR) spectroscopy are widely employed for drug discovery, quality control, and structural elucidation. Knowledge Gap: Despite their extensive use, limitations persist, such as spectral complexity, overlapping bands, and the need for costly instrumentation, leaving room for improvement in sensitivity, efficiency, and cost-effectiveness. Aims: This study aims to consolidate the principles, applications, and advancements of key spectroscopic methods in pharmaceutical analysis while highlighting emerging trends to overcome existing limitations. Results: The analysis demonstrates that UV-Visible spectroscopy provides high-speed, non-destructive analysis for drug quantification; FTIR offers qualitative and quantitative insights into functional groups; and NMR remains unparalleled for structural determination. Recent advancements include the integration of spectroscopy with machine learning for enhanced data interpretation and the development of hybrid techniques to improve sensitivity. Novelty: The study underscores the evolution of spectroscopy into a cornerstone of modern pharmaceutical analysis, driven by technological innovation and regulatory emphasis on accurate, reliable methods. Novel applications in drug design, impurity profiling, and real-time monitoring further exemplify its versatility. Implications: These findings emphasize the necessity of continued research into cost-effective, automated spectroscopic techniques to enhance pharmaceutical quality and safety, meeting the growing demands of global healthcare. Spectroscopy's integration into regulatory frameworks and novel drug development processes cements its role as a critical tool for advancing pharmaceutical science. Highlights: Spectroscopy ensures drug quality, purity, and safety in pharmaceuticals. UV-Vis, FTIR, and NMR are key for structural and impurity analysis. Innovations improve accuracy, efficiency, and broaden applications in drug analysis. Keywords: pectroscopy, Pharmaceutical Analysis, UV-Vis, FTIR, NMR